IMPACT OF HUMAN RECOURSES IN TOURISM MANAGEMENT - Atoeva Djalolitdinovna, Makhliyo (Journal of Geography, Regional Planning and Development, 2024)
General Background: Human resources play a critical role in the competitive advantage of tourism organizations, making HR management a key issue for the industry. Specific Background: A performance management model tailored to individual business and employee needs is vital for organizational success. Knowledge Gap: Despite the importance of HR in tourism, challenges such as recruiting skilled talent, excessive turnover, safety risks, and inadequate training persist, particularly in developing countries. Aims: This study aims to examine HR management constraints in the tourism industry and propose actions to address these challenges. Results: Semi-structured interviews with eight HR managers from large hospitality firms identified four key problem themes: recruitment of talented staff, high turnover, safety and welfare risks, and inadequate training infrastructure. The findings support strategic HRM theory, which asserts that deficiencies in human capital acquisition, retention, and development hinder organizational growth, productivity, and service quality. Novelty: A framework was developed to explore the relationship between tourism and HRM, followed by interviews to investigate how the industry recruits and retains employees with the right skills, knowledge, and attitudes. Implications: The findings highlight the need for increased public and private investment in tourism education, safety standards, and company-level development programs as priorities to overcome HRM constraints in developing countries.